Thiamine deficiency secondary to intestinal surgery leading to shoshin beriberi and Wernicke encephalopathy: a case report - Huang, Peiyu; Chen, Junyu; Deng, Zhixuan; Yang, Weiguo (Frontiers in Pediatrics, 2025)
PurposeThiamine is an essential micronutrient, and its deficiency, also known as beriberi, can have significant clinical implications. Thiamine deficiency impairs oxidative metabolic pathways, leading to reduced adenosine triphosphate (ATP) synthesis and energy production. This deficiency primarily affects energy-demanding organs, such as the brain and heart, resulting in central and peripheral neuropathies, severe metabolic acidosis, or even circulatory failure. Due to its nonspecific clinical presentation, thiamine deficiency is often misdiagnosed or overlooked, making early recognition and intervention critical for improving outcomes.Case reportThis report describes a case of shoshin beriberi with concurrent neurological involvement caused by thiamine deficiency following intestinal surgery. Remarkably, the patient's condition improved significantly with timely thiamine supplementation.ConclusionIn individuals at high risk of thiamine deficiency, such as those with prolonged fasting, gastrointestinal disorders, or chronic malnutrition, early identification and timely intervention are crucial for improving prognosis and reducing mortality. Early recognition and treatment are critical to reducing mortality associated with this condition.